"Childhood overweight and obesity: maternal perceptions of the time for engaging in child weight management" - Warschburger Petra; Kröller Katja (BMC, 2012)
Abstract Background There is an increasing awareness of the impact of parental risk perception on the weight course of the child and the parent's readiness to engage in preventive efforts, but only less is known about factors related to the parental perception of the right time for the implementation of preventive activities. The aim of this study was to examine parental perceptions of the appropriate time to engage in child weight management strategies, and the factors associated with different weight points at which mothers recognize the need for preventive actions. Methods 352 mothers with children aged 2-10 years took part in the study. We assessed mothers' perceptions of the actual and preferred weight status of their child, their ability to identify overweight and knowledge of its associated health risks, as well as perceptions of the right time for action to prevent overweight in their child. A regression analysis was conducted to examine whether demographic and weight related factors as well as the maternal general risk perception were associated with recognizing the need to implement prevention strategies. Results Although most of the parents considered a BMI in the 75th to 90th percentile a valid reason to engage in the prevention of overweight, 19% of the mothers were not willing to engage in prevention until their child reached the 97th percentile. Whereas the child's sex and the identification of an elevated BMI were significant predictors for parents' recognition of the 75th percentile as right point to engage in prevention efforts, an inability to recognize physical health risks associated with overweight silhouettes emerged as a significant factor predicting which parents would delay prevention efforts until a child's BMI reached the 97th percentile. Conclusion Parental misperceptions of overweight and associated health risks constitute unfavorable conditions for preventive actions. Feedback on the health risks associated with overweight could help increase maternal readiness for change.